2007
DOI: 10.2134/jeq2006.0477
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine Degradation and Residues Distribution in Two Acid Soils from Temperate Humid Zone

Abstract: Mineralization of atrazine and formation of extractable and non-extractable "bound" residues were followed under laboratory conditions in two contrasting soils (organic C, texture, and atrazine application history) from northern Spain. The soils, a Humic Cambisol (MP) and a Gleyic Cambisol (G) were incubated with labeled atrazine (ring-13C atrazine) at field application dose and measurements were made at different time intervals during 3 mo. Fate and behavior of atrazine along the incubation showed different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
5
0
3
Order By: Relevance
“…The enzymatic activity values, more influenced by soil depth (16-67% of variance) than by tillage system (11-37% of variance), were lower than those obtained for agricultural soils from temperate humid zone of NW Spain (Díaz-Raviña et al, 2005;Mahía and Díaz-Raviña, 2007;Mahía et al, 2011) but lied in the reported range for other Spanish soils in the semiarid and arid zones (Madejon et al, 2007;Madejon et al, 2009;Melero et al, 2012). Higher values were exhibited by the 0-5 cm layer of soil samples with higher organic matter content, which seems to indicate that the main soil property determining biochemical properties levels is the organic matter content.…”
Section: Discussionmentioning
confidence: 61%
“…The enzymatic activity values, more influenced by soil depth (16-67% of variance) than by tillage system (11-37% of variance), were lower than those obtained for agricultural soils from temperate humid zone of NW Spain (Díaz-Raviña et al, 2005;Mahía and Díaz-Raviña, 2007;Mahía et al, 2011) but lied in the reported range for other Spanish soils in the semiarid and arid zones (Madejon et al, 2007;Madejon et al, 2009;Melero et al, 2012). Higher values were exhibited by the 0-5 cm layer of soil samples with higher organic matter content, which seems to indicate that the main soil property determining biochemical properties levels is the organic matter content.…”
Section: Discussionmentioning
confidence: 61%
“…Other studies have also found a higher degree of atrazine as well as triazine amine ageing in topsoils compared to subsoils (Kruger et al 1997;Hang et al 2005;Godskesen et al 2005), which has been related to a larger fraction of organic matter in A horizons (Chung and Alexander 2002). Bound residues of atrazine have been found to be present in the fraction with highest organic matter content in several studies (Barriuso and Koskinen 1996; Loiseau and Barriuso 2002;Hang et al 2005;Mahía and Díaz-Raviña 2007). In the present study, the carbon contents were 2.58 % in the A horizon and 0.19 % in the C horizon (Table 1).…”
Section: Resultsmentioning
confidence: 83%
“…This has also been observed in some of the halogenated phenylura herbicides such as methabenzthiazuron, diuron, metobromuron and monuron (Berger 1999). As result some of the compounds most frequently used such as atrazine and isoproturon are frequently detected in surface and ground waters (Yassir et al 1999;Mahia and Diaz-Ravina 2007;Sørensen et al 2003).…”
mentioning
confidence: 82%